PERANAN PERENCANAAN TERHADAP PENDAPATAN UNIVERSITAS 17 AGUSTUS 1945 SAMARINDA - Sudiyarti Sudiyarti (Universitas 17 Agustus 1945 Samarinda, 2013)
The aim of this research is to know the influence of the salary to develop the career of the personnel of the University of 17 Agustus 1945 Samarinda. The focus of it is the salary of the staff and lecturer. The location of the research is in the University of 17 Agustus 1945 Samarinda. The method of it is qualitative one. The duration of it is one month namely in February 2013. The result of it is that in the year of 2013 the Education foundation 17 Agustus 1945 Samarinda has a very good decision to improve the salary of the staff and lecturer as well. Now they are very happy to work because it. They have a good income for his their living because they can build a welfare family. The year before they had just a very little money which is not enough to live with their family so they were very hopeless.